A new combination in Mirandea (Acanthaceae) - Daniel, Thomas F. (Instituto de Ecología, A.C., 2003)
Based on macromorphological, palynological, and preliminary molecular data, Pachystachys nutans Nees is transferred to Mirandea. The species is described and lectotypified. A key to the six species of this wholly Mexican genus is provided.